(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
About some ancient architectural structures built in the territory of ancient Termez and some of which have survived to the present day, about ancient and modern culture, which is a material applied art such as pottery, ancient temples, architectural elements related to ancient architecture and urban planning and their place in the architecture of the new period. In this way, we wanted to present the ancient city centers, city walls, residential areas, lifestyle, labor activity of the population, waterworks, as well as their place in modern architecture, to those interested in the field. Providing information about our ancient architecture and urban planning will increase the interest of students in the field of architecture, urban planning, architecture of buildings, design and construction of bridges, roads, waterworks. We wish science-hungry students and young professionals the best of luck in their research into history and the creation of the architecture of the future!